1939
DOI: 10.1093/oxfordjournals.aje.a118469
|View full text |Cite
|
Sign up to set email alerts
|

Normal Urinary Fluorine Excretion and the Fluorine Content of Food and Water1

Abstract: Since the original discovery of fluorine in the enamel of teeth by GayLussac and Berthollet (1) in 1805, fluorine has been found to be a usual constituent of plant, animal and human tissues. This fact is an almost necessary corollary of the extremely widespread occurrence of fluorine in soils and waters. With the exception of the bones and teeth, the amounts found in the tissues of man or animals without specific fluorine exposure are usually small; in our experience generally less than 1 milligram per kilogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1942
1942
1979
1979

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…The amount of fluorine in the coarse (I) and fine (II) corn diets was considerably lower (0.4 p.p.m.) and of the same order as obtained for common cereals by Machle, Scott, and Treon (13).…”
Section: Tsupporting
confidence: 79%
“…The amount of fluorine in the coarse (I) and fine (II) corn diets was considerably lower (0.4 p.p.m.) and of the same order as obtained for common cereals by Machle, Scott, and Treon (13).…”
Section: Tsupporting
confidence: 79%
“…Machle [1936], Machle and Largent [1943] and Machle et al [1939Machle et al [ , 1942 mea sured urinary F in 130 adult subjects and found a mean of 1.00 ppm (range 0.5-2.8 ppm). Their studies indicated that uri nary F excretion could be utilized as a mea sure of ingestion and F storage, even at very high levels of intake.…”
Section: Discussionmentioning
confidence: 99%
“…Available evi dence indicates that urine F measurements in a population drinking water with a F con centration ranging from 0.3 to 1.0 ppm or higher can be used to predict the water F level with confidence [Machle, 1936;Machle et al, 1939;McClure and Kinser, 1944;Largent, 1954], There is, however, some controversy concerning the water F-urine F correlation in a population ingesting water with very low F levels. Investigators have studied in dividuals drinking water containing 0.06-1.36 ppm F and have found the mean uri nary F concentration to range from 0.06 to 1.12 ppm [Smith et al, 1950].…”
mentioning
confidence: 99%
“…A detailed study has been made of the toxicity of the nitroparaffins, and in this respect they are similar to the ester-type solvents of approximately equal vapor pressure (6,8,9), They therefore offer no unusual hazards, either with respect to toxicity or flammability. The ordinary precautions exer-cised in handling the common lacquer solvents are sufficient for the nitroparaffins.…”
Section: Solvents Inmentioning
confidence: 99%